Literature Review Pijat Punggung untuk Mengurangi Nyeri Persalinan Kala I - Hidayati, Ulfah (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2024)
First stage labor is often associated with pain due to uterine contractions, dilation and effacement of the cervix. This article aims to determine whether back massage can reduce first stage labor pain. The article was written using a literature review method using electronic databases, namely PubMed and ScieneDirect with the keywords